PROTECTIVE EFFICACY OF Moringa oleifera AGAINST RADIATION AND MERCURIC CHLORIDE INDUCED HAEMATOLOGICAL CHANGES IN MICE - PANCHARIYA, MURALIDHAR; KHATRI, POOJA RANI; PUROHIT, R. K.; AGARWAL, MANISHA; CHAKRAWARTI, ARUNA; MITTAL, DEEPAK (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The present study was planned to investigate the impact of the Moringa oleifera against combined administration of mercuric chloride and radiation on haematogical changes in mice. The mice were exposed to mercuric chloride (0.5 ppm) and gamma radiation (2.0Gy) simultaneously and individually. The experimental groups were given Moringa oleifera seven days prior to radiation or mercuric chloride treatment. The changes included increase or decreae in the various heamatological parameters viz. RBC, WBC, Hb, MCH, MCHC etc. In the combined treatment groups the changes were more severe showing synergistic effect. An early and fast recovery in Moringa pre-treated groups may be due to the protection provided by the drug.